Factors Influencing Consumer Impulsive Buying Behavior regarding Mobile Game Purchase Intention - Jen-Chieh Chung; Ying-Hsiao Lai; Yu-Tzu Chang (Engineering Proceedings)
We explored impulsive buying behavior regarding mobile games and the factors influencing it. Data were collected from 389 participants. The results presented differences between different types of impulse buying. The findings contribute to the future study of consumer behavior and provide implications for commercial providers.